2021
DOI: 10.1016/j.bioactmat.2021.02.039
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of sirtuin 3 on titanium particle-induced osteogenic inhibition by regulating the NLRP3 inflammasome via the GSK-3β/β-catenin signalling pathway

Abstract: Periprosthetic osteolysis (PPO) remains the key factor in implant failure and subsequent revision surgery and is mainly triggered by wear particles. Previous studies have shown that inhibition of osteoblastic differentiation is the most widespread incident affecting the interface of trabecular and loosening prostheses. Additionally, the NLRP3 inflammasome is activated by prosthetic particles. Sirtuin3, an NAD + -dependent deacetylase of mitochondria, regulates the function of mitochondri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 46 publications
4
24
0
Order By: Relevance
“…However, for the activation of NLRP3 and AIM2, SIRT3 is not necessary [ 112 ]. However, in a study conducted by K Zheng et al [ 113 ] on Ti-induced osteolysis of rat femurs, it was found that depletion of SIRT3 enhanced the activation of the NLRP3. The researchers also confirmed that the expression of SIRT3 in the revision TJA was significantly lower than that in the primary TJA through the investigation of clinical samples.…”
Section: Pyroptosis In Osteoblastmentioning
confidence: 99%
“…However, for the activation of NLRP3 and AIM2, SIRT3 is not necessary [ 112 ]. However, in a study conducted by K Zheng et al [ 113 ] on Ti-induced osteolysis of rat femurs, it was found that depletion of SIRT3 enhanced the activation of the NLRP3. The researchers also confirmed that the expression of SIRT3 in the revision TJA was significantly lower than that in the primary TJA through the investigation of clinical samples.…”
Section: Pyroptosis In Osteoblastmentioning
confidence: 99%
“…Therefore, the SIRT3 and SOD2 may form an important regulatory network to protect osteoblasts against the cytotoxic of TiO2NPs ( 94 ). Besides, upregulation of SIRT3 significantly attenuates the titanium particle-induced inhibition of osteogenesis by inhibiting the NLRP3 inflammasome ( 95 ). To sum up, SIRT3 plays a protective role in bone formation and maintaining bone homeostasis.…”
Section: The Role Of Sirt3 In Bone Remodeling and Osteoporosismentioning
confidence: 99%
“…In contrast, the inhibitor of the TGF-β/Smad2/3 pathway did not affect the activation of ERK1/2, indicating that the activation effect of the ERK1/2 pathway triggered by TGF-β2 on regulating EMT was not controlled by the TGF-β/Smad pathway. Glycogen synthase kinase-3β (GSK-3β), a serine/threonine kinase widely found in mammalian cells, is closely related to cell proliferation, apoptosis, migration, and EMT [ [21] , [22] , [23] ] and can phosphorylate, ubiquitinate, or degrade transcription factors, including Snail and Slug to maintain epithelial phenotypes [ 24 , 25 ]. Therefore, we infer that when GSK-3β is phosphorylated and inactivated, the degradation of a range of downstream transcription factors, such as Snail and Slug, is limited, which can promote the development of EMT.…”
Section: Introductionmentioning
confidence: 99%